The politeness prosody of the Javanese directive speech - Rahyono, F. X. (UI Scholars Hub, 2009)
This experimental phonetic research deals with the prosodies of directive speech in Javanese. The research procedures were: (1) speech production, (2) acoustic analysis, and (3) perception test. The data investigated are three directive utterances, in the form of statements, commands, and questions. The data were obtained by recording dialogues that present polite as well as impolite speech. Three acoustic experiments were conducted for statements, commands, and questions in directive speech: (1) modifications of duration, (2) modifications of contour, and (3) modifications of fundamental frequency. The result of the subsequent perception tests to 90 stimuli with 24 subjects were analysed statistically with ANOVA (Analysis of Variant). Based on this statistic analysis, the prosodic characteristics of polite and impolite speech were identified.